Czy Lechoń w "Duchu na seansie" kompromitował poezję romantyczną i mitologię narodową? - Ratajska, Krystyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
In the article, composed of two parts with the titles Spektakl modernistyczny czy seans spirytystyczny? (A modernist spectacle or a spiritistic seance?) and Dlaczego Słowacki niszczy konterfekt księcia Józefa? (Why does Słowacki destroy the portrait of Prince Józef?), presents a contextual interpretation of Jan Lechoń’s poem Duch na seansie (A Ghost at a Seance). The author questions the opinion, which was widespread in literary criticism, that Lechoń together with other members of the Skamander group discredited Romantic poetry and national mythology on the threshold of independence. The analysis of the poem made in the article leads to the conclusion that the poet fought stereotypes deeply rooted in public opinion, which in the eyes of the general public were also reinforced by Slowacki’s poetry. Thus, Słowacki appears at the seance to demystify a belief in the messianic, necrotic and patriotic tone of his poetry, in the bard-creator of the national Gospel, who is endowed with the power to discover absolute truths, and in the „master of the word” as well as the „creator of artistic beauty” as well as the only generally-accepted opinion.Optimistic signs of revival have dominated the symbols of suffering, the talkativeness has been replaced by silence, the word by the iconoclastic deed, the mystical heat by ironic distance. The symbols, images, references to literary texts and other signes of culture help to create a revalued portrait of Słowacki and mould a myth of gray heroism, which is a complete contrast to the myth of the „colourful uhlan” . The destruction of the portrait of Prince Józef Poniatowski and a reference to Piłsudski found in the last line of Karmazynowy poemat (The Crimson Poem) are the signs of the ideological declaration of the young poet, who referring to great Romantic tradition, discovers new and new meanings.